Caracterização das condições atmosféricas no período 1991-2007 em cidades que compõem a calha do Rio Solimões-Amazonas. - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
The study of small and medium cities in the Amazon State shows profiles of important economic and social structure for the Western Amazon. The functions performed by these cities show an interesting role if linked to weather conditions. This study aimed to characterize the atmospheric circulation of the main phenomena of time in cities in the gutter of the Solimoes-Amazon River, from 1991 to 2007, analyzed by two variables: rainfall and wind. The cities selected were Benjamin Constant, Fonte Boa, Tefé, Coari, Codajás, Manaus, Itacoatiara and Parintins. In an attempt to understand whether there were variations in meteorological variables due to the quantitative population affecting the weather of each city, a literature review of the main precipitation systems operating in the region since the large-scale circulation was carried out, mesoscale and synoptic. The methodology was based on data from the National Institute of Meteorology (for precipitation) and reanalysis data (for wind). Owing to lack and absence of data in the series studied it was necessary to apply the technique of filling of flaws based on statistical calculations of linear regression from which the CPC data were evaluated and used to replace the missing data. The main results allowed to create a temporary climatological normal (1991-2000) and compare the values to each city under study. The results of the wind showed the presence and the displacement of the Bolivian High (AB) at high levels in the troposphere during the months of September, October and November (the period close to the wet season) showing its influence in the rainfall. Given the values of precipitation and wind for characterization of atmospheric conditions in the gutter of the river, for further analysis it is necessary to check other climate elements: temperature, relative humidity, atmospheric pressure, etc.
Keywords: Amazônia Ocidental; Clima; Cidades; Precipitação Pluvial; Vento; Western Amazon; Climate; Cities, Rainfall; Wind.; CIÊNCIAS HUMANAS: GEOGRAFIA